2018
DOI: 10.1037/spq0000243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of data points per x- to y-axis ratio on visual analysts evaluation of single-case graphs.

Abstract: Research based on single-case designs (SCD) are frequently utilized in educational settings to evaluate the effect of an intervention on student behavior. Visual analysis is the primary method of evaluation of SCD, despite research noting concerns regarding reliability of the procedure. Recent research suggests that characteristics of the graphic display may contribute to poor reliability and overestimation of intervention effects. This study investigated the effect of increasing or decreasing the data points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 14 publications
4
73
0
Order By: Relevance
“…First, the DPPXYR recommendations are preliminary and are based on one empirical study; thus, researchers may not see the justification for this metric until additional data support the current guidelines. Second, the initial empirical study (Radley et al., 2018) and subsequent guideline paper (Dart & Radley, 2018) were published in the field of school psychology. Authors may not yet be aware of these recommendations, particularly considering that our parameters for this search focused on four journals in the field of special education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the DPPXYR recommendations are preliminary and are based on one empirical study; thus, researchers may not see the justification for this metric until additional data support the current guidelines. Second, the initial empirical study (Radley et al., 2018) and subsequent guideline paper (Dart & Radley, 2018) were published in the field of school psychology. Authors may not yet be aware of these recommendations, particularly considering that our parameters for this search focused on four journals in the field of special education.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that graphical elements that are classified as either aesthetic‐altering or analysis‐altering can be re‐categorized based on additional empirical evidence. Currently, there is preliminary evidence to suggest that two graphical elements are analysis‐altering: (1) the process used to scale the ordinate (Dart & Radley, 2017), and (2) the proportions of the abscissa (i.e., x ‐axis) length to the ordinate length (Radley et al., 2018). Thus, these elements are the focus of this project.…”
Section: Use Of Scrd In Ld Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigate the prevalence of biases by searching for distinct patterns of deviations in judgment and decision accuracy with largely mixed results. Through a total of seven cognitive psychology experiments, Sun et al (2010Sun et al ( , 2016 and Radley et al (2018) find that varying scale proportions in graphs change the resulting decision-making since data points are evaluated in a cognitively biased manner based on their distance to other chart elements. Furthermore, Padilla et al (2015) demonstrate that uncertainty is understood to a disparate extent when it is encoded through spatial glyphs, color, or brightness.…”
Section: Prevalence Of Biasesmentioning
confidence: 99%
“…To address the aforementioned limitations with using equal-interval graphs, some researchers have developed systematic protocols to aid evaluation of graphs (e.g., Wolfe et al, 2019), others have developed additional statistics or graphic aides (e.g., trend lines) to assist visual interpretation of data (e.g., Fisher et al, 2003;Lane & Gast, 2014;Lane & Sándor, 2009;Manolov & Vannest, 2019), and some suggest more intensive training (e.g., Blair et al, 2019;Nelson et al, 2017;O'Grady et al, 2018;Young & Daly, 2016). Additionally, many researchers have suggested that data should be graphed using basic principles of standardization in the construction of visual displays (e.g., Dart & Radley, 2017;Datchuk & Kubina, 2011;Kubina et al, 2017;Lindsley, 1992;Pennypacker et al, 2003;Radley et al, 2018). Put simply, standards applied to a graphic display allow less room for distortion and misinterpretation due to faulty graph construction (Cleveland, 1994, Dart & Radley, 2017Huff, 1954;Kubina et al, 2017;Tufte, 2001).…”
Section: Equal-interval Graphs and Semi-logarithmic Graphsmentioning
confidence: 99%